DIGITALIZING EDUCATION AS AN EDUCATIONAL TOOL FOR TEACHING IN EXTRAORDINARY CIRCUMSTANCES - Marković, Sanja Anastasija (Ekonomija - teorija i praksa, 2022)
This paper will analyze the implementation of video lectures as a new form of teaching material which could play an important role in situations when it is necessary to adopt online education, as was the case during the global pandemic caused by the SARS-COV-2 virus. In addition to video lectures, our students were given access to a course book and PowerPoint presentations which included voice recordings of the instructor. The students took part in a survey to identify the form of teaching they found to be most useful. The results were analyzed in this paper, and a classification made in an attempt to answer the question of whether video presentations are a sound investment. The prioritization of the criteria on which to base the evaluation of the educational methods included in the teaching process will be carried out using the PIvot Pairwise RElative Criteria Importance Assessment – the PIPRECIA method